Strategic Factor Development Management that Affects Being a Learning Organization of the Local Government Organization: Strategic Factor Development Management that Affects Being a Learning Organization of the Local Government Organization - Okapanom , Santi; Phosing, Phakdee; Yupas, Yupaporn (RATANABUTH JOURNAL, 2023)
Local government organizations need to adjust their strategies to facilitate knowledge transfer within and outside the organization. The key objective is to establish the best practices for efficient work performance. The purpose of this research is to study the factors that influence the strategic management of local government organizations as learning organizations. It aims to investigate the factors that affect the organization’s learning capability and to create and validate a model for the organization as a learning organization within the local government authorities in the Northeastern Region of Thailand. The population and sample groups include 324 individuals consisting of administrators and staff working in local government organizations. The study will utilize the Yamane formula and employ stratified random sampling. The tools used will include a questionnaire with a confidence level ranging from .711 to .875. The statistical techniques employed will include mean, standard deviation, and multiple regression analysis. The research findings indicate that the overall average of strategic management factors influencing the organization as a learning organization for local government organizations is ( = 3.28). The predictive factors for the organization as a learning organization can be summarized into eight dimensions, namely: participation in management, vision, teamwork, strategy, knowledge management, commitment, personnel development, and technology. The respective regression coefficients (ß) for these dimensions are .246, .327, .120, .147, .113, .102, .118, and -.120. The prediction rate is 74.5% in order of magnitude. The model of the local government organization as a learning organization in the Northeastern Region emphasizes the importance of utilizing information technology as a key tool for management. It also highlights the significance of teamwork to elevate the organization’s status as a recognized learning organization. Furthermore, it stresses the necessity of developing essential skills and knowledge for personnel in utilizing technology for knowledge management. Importantly, the active involvement of personnel within the organization is crucial in driving the advancement of the organization as a learning organization model.